Strategi Pembelajaran Matematika Dikembangkan dengan Mempertimbangkan Karakteristik Siswa Sekolah Dasar - Pasaribu, Siti Rahmayani; Sofiyah, Khotna (LANCAH: Jurnal Inovasi dan Tren, 2024)
Understanding students as one of the teaching competencies can help in describing learning strategies, as well as in determining attitudes towards interactions with other students. Each student has unique characteristics and experiences individual development. Characteristics of students in elementary school (aged 6-12 years) according to the intellectual growth phase. This phase begins when children achieve the ability to think critically and build logical connections, enabling them to make decisions based on coherent reasoning. A comprehensive understanding of the characteristics demonstrated by elementary school students is critical in fostering successful mathematics learning efforts. This narrative offers a literature review that focuses on mathematics learning strategies adapted to the characteristics of elementary school students